The Struggle of the Shi'is in Indonesia - Zulkifli (ANU Press, 2013)
The Struggle of the Shi'is in Indonesia is a pioneering work. It is the first comprehensive scholarly examination in English of the development of Shiism in Indonesia. It focuses primarily on the important period between 1979 and 2004 - a period of nearly a quarter of a century that saw the notable dissemination of Shi'i ideas and a considerable expansion of the number of Shi'i adherents in Indonesia. Since Islam in Indonesia is overwhelmingly Sunni, this development of Shiism in a predominantly Sunni context is a remarkable phenomenon that calls for careful, critical investigation. There is also an important examination of the principal ideas underlying the Madhab Ahl al-Bayt, the Imamate and Imam Madhi, Ja'fari jurisprudence and ritual piety. Appropriately, in his discussion, Zulkifli provides a succinct outline of contrasts with Sunni ideas and practice. He also examines the publishing efforts that underpinned the dissemination of Shi'i ideas and the founding of IJABI (Ikatan Jamaah Ahlul Bait Indonesia) in July 2000 for the propagation of Ahl al-Bayt teachings. Given the Indonesian context, Zulkifli is also concerned with Sunni reactions to these Shi'i developments - a story that continues to unfold to the present. This book as a work of great value and significance for the continuing understanding of the richness and complexity of Indonesian Islam.